PSXV-23 The effect of Bacillus subtilis or Ehinacea on growth performance, meat quality and immune indexes in lambs. (7th December 2018) - Wu, J; Song, S; Wang, C; Pan, F; Casper, D; Zhang, L; Lang, X; Gong, X; Wang, F; Liu, L
Abstract: The objective was to determine if feeding Bacillus Subtilis or Echinacea to growing lambs for 60 d improved growth performance, nutrient digestibility, serum biochemical indexes, diarrhea rate, carcass traits, meat quality, and organ indexes. Twenty-seven male Suffolk X Small Tailed Han lambs were blocked by body weight into 3 lambs per pen with pens assigned to one of three treatments: lambs were fed a Control (no additive); or 100 mg/kg/d Bacillus subtilis, or Echinacea, respectively. All data were analyzed as a randomized complete block design. Feeding lambs Bacillus subtilis and Echinacea resulted in similar (P > 0.05) average daily gains, dry matter intake (DMI), and feed conversions compared to lambs fed the Control, but the lambs fed Bacillus subtilis decreased (P < 0.05) DMI compared to lambs fed Echinacea. Feeding lambs Bacillus subtilis increased (P < 0.05) apparent total tract nutrient digestibility of DM, CP, fat, NDF, ADF compared to lambs fed Control and Echinacea. In contrast, lambs fed Echinacea demonstrated increase (P < 0.05) ADF digestibility compared to lambs fed Control and Bacillus subtilis. Feeding Bacillus subtilis reduced (P < 0.05) diarrhea incidence rate, alkaline phosphatase, blood urea nitrogen, albumin, triglycerides, and blood sugar levels, while increasing total protein, serum globulin, spleen index, and lung indexes compared to lambs fed Control. Lambs fed Echinacea had increased (P < 0.05) alkaline phosphatase and globulin, reduced blood urea nitrogen and albumin (P < 0.05) compared to lambs fed the control. Feeding lambs Bacillus subtilis resulted in similar (P > 0.05) carcass traits, muscle eye area, pH, CP, and fat concentrations compared to lambs fed Control and Echinacea, but shear force, and moisture content were reduced (P ＞ 0.05), which increased (P < 0.05) cooking rate. Lambs fed Bacillus subtilis demonstrated improved nutrient digestibility, immunity, and meat quality. Key Words: